If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4 + -2s) + -6s = 3 (4 * 7 + -2s * 7) + -6s = 3 (28 + -14s) + -6s = 3 Combine like terms: -14s + -6s = -20s 28 + -20s = 3 Solving 28 + -20s = 3 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -20s = 3 + -28 Combine like terms: 28 + -28 = 0 0 + -20s = 3 + -28 -20s = 3 + -28 Combine like terms: 3 + -28 = -25 -20s = -25 Divide each side by '-20'. s = 1.25 Simplifying s = 1.25
| 56x^2-9x-81= | | L=5w-3 | | 9(a+5.8)+8.2a=5 | | 45a+172= | | 541x=64 | | 64x-541=-803 | | -x^2-9x+3=0 | | 180=13x-8+3x+7x+4 | | 9a^2+12a+7=0 | | ln(x(x-10))=5 | | 541x=803 | | -4d-6=-6d-4 | | 541x-803=64 | | 10-2q=8 | | 3+34+674= | | 30(50x+20)+40=200 | | 8*o=98 | | 5x-4+7x-18=8x+2 | | r/6+r/6=5 | | 2(2x-3)=5x-11 | | -5x^2+250x-130000=5000 | | (x^2)-19x+9.5=0 | | (x+18)=688 | | 0.4(x+7)-0.1(3x+6)=-0.8 | | 17+20-3=17y | | y=6xt+5xt^2+6 | | 15d+3.2=92 | | 3(5-3)=2(3-1) | | 2+3/5x=9 | | 4(8-2x)=-6x+4(x-4) | | 10=5-12z | | 27*n= |